Internal polar field enhanced H2 evolution of BiOIO3 nanoplates. (29th June 2016) - Su, Yang; Zhang, Ling; Wang, Wenzhong
Abstract: Internal polar field is found to be an original and effective method of separate photogenerated carriers and thus to enhance the efficiency of photocatalysis. Here, BiOIO3 nanoplate, as a pyroelectric material, is used to probe the influence of internal polar field effect on the separation of photogenerated carriers and photocatalytic H2 evolution. It is demonstrated that there is a 7-fold increase in the H2 evolution using 150 nm BiOIO3 nanoplates compared to 25 nm nanoplates in thickness. This achievement is ascribed to the increased internal polar field effect from the increased thickness of the BiOIO3 nanoplates. The internal polar field effect ensures a tightly bound layer of the absorbed ions on the surface of BiOIO3 nanoplates, and also acts as an accelerator to separate the photoexcited carriers. Both of these features contributed to the enhanced photocatalytic performance of H2 evolution. Graphical abstract: Highlights: Internal polar field within BiOIO3 nanoplate increases with its thickness. Internal polar field enhances the separation of photo-generated carriers. Internal polar field results in the up bending of conduction band of the BiOIO3 . The polar layer absorbed on surfaces of BiOIO3 helps the H2 evolution. We report a new photo-catalyst for the effective H2 evolution.